Longitudinal relationship between internet addiction and psychotic-like experiences among Chinese college students - Pu Peng; Hongyu Zou (Comprehensive Psychiatry)
Background: While previous cross-sectional studies have suggested a link between psychotic-like experiences (PLEs) and internet addiction (IA), longitudinal evidence remains scarce. This study aimed to explore the prospective relationship between IA and PLEs among college students. Method: A total of 636 college students (80 % female) were assessed in November 2022 and again one year later. IA was measured using the Internet Addiction Diagnosis Questionnaire (IADQ), and PLEs were assessed with the 16-item Prodromal Questionnaire (PQ-16). Demographic, psychological, and environmental factors were collected and controlled. Multiple logistic regression and cross-lagged panel analyses examined the longitudinal associations between IA and PLEs. Results: At baseline, the prevalence of IA and PLEs was 11.3 % and 16.8 %, respectively. Higher baseline IADQ scores (Adjusted odds ratio = 1.035; 95 % confidence interval = 1.002–1.069; p = 0.036) were independently associated with an increased risk of PLEs at follow-up, while baseline PQ-16 scores were not linked to later IA. Cross-lagged panel analysis revealed that IA at baseline predicted later PLEs (β = 0.082, p = 0.043), whereas baseline PLEs did not predict IA (β = 0.049, p = 0.255). Specifically, IA predicted unusual thoughts (β = 0.122, p = 0.003) and negative PLEs (β = 0.111, p = 0.008), but not perceptual abnormalities (β = 0.040, p = 0.301). Conclusion: IA may be an independent risk factor for PLEs in college students, particularly for unusual thoughts and negative PLEs, but not for perceptual abnormalities. Targeted interventions addressing IA may help reduce PLEs.